The Drivers of Business Performance: Does Sales Force Strategy and Network Capability Matter? - Ahmad Johan; Zulganef Zulganef; Sri Astuti Pratminingsih (Universitas Muhammadiyah Yogyakarta, 2023)
Many factors that SMEs must consider in driving their business to achieve success. This study attempts to identify and analyze the factors that can encourage the business performance of SMEs by considering sales force strategy and network capability. This study also examines the mediating role of network capability in the influence of sales force strategy on business performance. This study used a quantitative approach, with 140 creative SMEs in Bandung, West Java, as the respondents. The data was collected using a survey and further analyzed using regression and path analysis with SPSS 25 software. The findings indicated that sales force strategy and network capability positively influenced business performance and that sales force strategy influences network capability. Furthermore, this study confirmed that network capability mediated the relationship between sales force strategy and business performance. This study provided implications for both practice and theory.